A review of important cognitive concepts in aviation. Issue 2 (2nd April 2016) - Martins, Ana P. G.
Abstract: Even considering the current low accident rate in aviation, the anticipated growth in the number of airplanes in the air in the next decades will lead to an inadmissible rise in the number of accidents. These have been mostly attributed to human error and a misunderstanding of automation by the crew, especially during periods of high workload and stress in the cockpit. Therefore, increased safety requires not only advances in technology, but improved cockpit design including better human-machine interface. These cannot be achieved however, without considering some of the cognitive constructs that affect the behaviour of pilots in the cockpit. In fact, given its characteristics and public visibility, the flight deck of commercial jets is one of the most common arenas for the study of complex and skilled human performance. Here I present a literature review on the selected topics of workload, situation awareness, stress and automation in the cockpit, with the goal of supporting the development of new technologies.